Use of Ascetic Fluid Cholesterol as a Marker to Differentiate between Types of Ascetic Fluid - Ali, Sadiq Jabar; AlKhersan, Hasan Ali; Mahdi, Hamed S. (AL-Kindy College Medical Journal, 2008)
Background:- Cholesterol is high in ascetic fluid dueto malignancy and other causes of exudates.Objective:-To use cholesterol as a marker todifferentiate between exudative and transudativeascetic fluid and to compare that with other routineparameters.Methods:-Twenty eight patients were included in thisstudy 17 females with mean age of 41.9 years, 11males with mean age of 48.2 years. The patients weredivided in group I suspected transudate, and group IIsuspected exudate according to history and clinicalexamination.Ascetic fluid samples were sent for total protein,albumin, and cholesterol measurement blood sampleswere sent for serum protein and albumin measurement.Results:-In this study ascetic fluid cholesterol was fitwith history and clinical examination to differentiatebetween exudative and transudative ascetic fluid.Cholesterol was a good marker when compared withascetic fluid total protein and ascetic serum proteinratio in group I, but not in the others.Conclusion: - cholesterol can be used as a marker forthe diagnosis of a cites cases but a large number ofpatients is important for accurate results